Combining abilities and heterotic patterns for heat tolerant traits in tomatoes (Solanum lycopersicum). (13th June 2022) - Ayenan, Mathieu Anatole Tele; Danquah, Agyemang; Hanson, Peter; Asante, Isaac Kwadwo; Danquah, Eric Yirenkyi
Abstract: This present study was undertaken to (i) assess the performance of hybrids under heat stress, (ii) determine the combining abilities of parental lines and their crosses, and (iii) identify the most efficient heterotic grouping method to classify the lines. We evaluated two sets of hybrids generated using the NC II design and a partial diallel mating design. Most crosses outperformed their parents and the best commercial hybrids for fruit weight per plant (FWP), fruit set (FS), fruit weight (FW), and the number of fruits per plant (NFP) under heat stress. The specific (SCA) and the general (GCA) combining ability variances were significantly higher than zero. The crosses Fla.7171 × P005 and CLN2026D × ATS020 had positive SCA effects and high per se performance for FW and FWP. BJ01 was the best combiner for FWP, NFP, and FS. The SNP‐based heterotic grouping was 28% more efficient than the heterotic grouping based on the GCA of multiple traits method and classified the lines into three groups. These findings provide a foundation for speeding up heat‐tolerant hybrid in tomatoes.